(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today 13.4% Indian women working on a regular salaries compared to 21.2% of working men Family health depends on educational level, health & nutritional status of women. Generally women either working or non working takes her food lastly and some times taken very small or inadequate. Two hundred working and non working women, aged 25 to 40 years, from Beed district were selected randomly. Four data collection methods were used the results of the study show that magnify of the samples were belonging to lower middle class and maximum no. of sample were educated. The anthropometrical measurements of the sample were increase after supplementation in group ’A’ whereas there was no increment in the anthropometrical measurements of group ’c’. Thus study have concluded that it should be necessary to educate both working and non working women about importance of nutrients & help them to reduce high risk of nutritional diseases.